Multi Keyword Search Within An Encrypted Text Using Tf-Idf Based Trapdoor Function - Soumya, L; Vamsi Krishna, BS (International Journal of Computer Sciences and Engineering, 2025)
Many people can save sensitive data on remote servers, provide data access from the admin to data users. As the stored information can hold important information, before uploading the data to the cloud, the information must be encrypted. If any cloud user wants to retrieve any file then they no need to check every file in the cloud. Data user can utilize keyword-based document retrieval. This paper suggests a technique to retrieve the encrypted information from the data store through multiple keywords. This technique instantaneously maintains active update operations like deleting as well as inserting records. Particularly, TFIDF is preferable for building index as well as generating query. Here we establish a tree-based file index to offer multi keyword ranked search. For encrypting and decrypting the files, AES algorithm is used and simultaneously offer the exact relevance score frequency among encrypted indexed files. In this technique, decryption can be performed before downloading the file from the database. General tests are directed to show the productivity of the proposed scheme.